Is Europe on track towards net zero mobility? - Tommaso Pardi (European Trade Union Institute (ETUI), 2024)
The purpose of this paper is to explore whether the 'Fit for 55' update of the European Union's CO₂ regulation is up to the task of fixing its past mistakes and putting Europe on course to reach net zero mobility by 2050, while also dealing with the new set of challenges that arises with the accelerated process of electrification. The paper's analysis indicates that it is not up to such a task. There is an urgent need to rectify the 'Fit for 55' update, and, more generally, the trajectory taken by the electrification path in Europe. There are, however, a few, key and relatively straightforward measures that could steer the production and sale of new cars in Europe towards a more sustainable, inclusive and efficient path. These include the phasing-out of the weight-based standards regime and its replacement with one geared rather better to energy efficiency; and to integrate lifecycle analysis into the regulatory regime so as to ensure that a car's full carbon footprint is taken properly into account. These measures together should steer the production and sales of new cars in Europe in the right direction: towards greener, more energy efficient, affordable, electric cars that are made in Europe. The paper concludes that systems of support need to be fundamentally reconfigured if electromobility systems are to be shaped more in the direction of affordability.
Keywords: 330; EU climate policy; Greenhouse gas emissions; Impact assessment; Electromobility; Energy saving; EU countries; EU-Klimapolitik; Treibhausgas-Emissionen; Wirkungsanalyse; Elektromobilität; Energieeinsparung; EU-Staaten